A Relational Study of Supply Chain Agility and Firms' Performance in the Services Providers - Bargshady, Ghazal; Chegeni, Ali; Kamranvand, Shayan; Zahraee, Seyed Mojib (International Review of Management and Marketing, 2016)
The link between agile supply chain dimensions and business performance in the Iranian service industry is assessed in this study. A questionnaire covering important agility criteria identified in the literature was designed and administered to a sample of 420 managers and users of supply chain in service providers. The response rate achieved was 16%. Validity and reliability were statistically tested. Line regression analysis was also used and all tests confirm normal distribution of data. By testing the full supply chain related with agile practices, the findings indicated there was a significant connection between supply chain agility and business performance such as user satisfactions, information systems and advertisement. Keywords: Supply Chain Agility; Firm Performance; Industrial Organization; Iranian Servies Industries JEL Classifications: E01, L16